2009
DOI: 10.21273/hortsci.44.3.800
|View full text |Cite
|
Sign up to set email alerts
|

Organic Fertilizers for Greenhouse Tomatoes: Productivity and Substrate Microbiology

Abstract: Organic fertilizer regimens consisting of combinations of composts (yard waste, swine manure, or spent mushroom substrate) and liquid fertilizers (fish- or plant-based) were evaluated against conventional hydroponic fertilizers in two experiments with greenhouse tomatoes grown in peat-based substrate. Crop yield and fruit quality were evaluated and several assays of substrate microbial activity and community profiles (fluorescein diacetate analysis and EcoLog, values, nematode counts) were conducted. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…have shown that the interactions between heavy metals and essential elements may supply the plants with significant quantities of nutrient elements as well as heavy metals and may thereby affect plant growth positively or negatively, depending on the type of interaction (synergistic or antagonistic). Like other vegetable crops, peppers (Capsicum annuum L.) can be cultivated on conventional substrates such as perlite, rockwool, sand, and other soilless systems, which have replaced the traditional crop grown in agricultural soil in the greenhouse (Zhai et al, 2009;Díaz-Pérez and Camacho-Ferre, 2010). Increasing awareness of the adverse economic and environmental impacts of conventional substrates has stimulated the interest in using organic wastes and agricultural by-products as substrates in soilless culture (Del Amor and Gómez-López, 2009;Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…have shown that the interactions between heavy metals and essential elements may supply the plants with significant quantities of nutrient elements as well as heavy metals and may thereby affect plant growth positively or negatively, depending on the type of interaction (synergistic or antagonistic). Like other vegetable crops, peppers (Capsicum annuum L.) can be cultivated on conventional substrates such as perlite, rockwool, sand, and other soilless systems, which have replaced the traditional crop grown in agricultural soil in the greenhouse (Zhai et al, 2009;Díaz-Pérez and Camacho-Ferre, 2010). Increasing awareness of the adverse economic and environmental impacts of conventional substrates has stimulated the interest in using organic wastes and agricultural by-products as substrates in soilless culture (Del Amor and Gómez-López, 2009;Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The stated goal of Rippy et al (2004) also was "to develop a certifiable organic regimen for growing greenhouse tomatoes that would be comparable with those grown conventionally with regard to production methods as well as nutritional status in leaf tissue, plant development, and harvest yields." In the present study, the compost tea, a liquid fertility amendment, had much lower macronutrient concentrations, with the exception of Mg, than the liquid organic fertilizer used by Zhai et al (2009), which was applied every 4 to 6 h. While the N content of tea was not measured in the present study, Hargreaves, Adl, and Warman (2009), using a similar compost from the same Lunenburg facility and the same steeping method, found 106 and 1.70 mg L −1 of nitrate (NO 3 -) and ammonium (NH 4 + ), respectively, which is much lower than NO 3 -content in liquid fertilizer (190 mg L −1 ) used by Zhai et al (2009). When obvious N and P deficiency symptoms were seen in the present study, no attempt was made to allay the deficiency; experimental protocol was maintained to examine availability of nutrients from MSW compost in a container environment and to attempt to verify or refute claims of compost tea benefits, whether applied to soil or foliage.…”
Section: Discussionmentioning
confidence: 43%
“…These leaf tissue concentrations were of a similar order as in the present study. Zhai et al (2009) grew tomatoes in the greenhouse using a peat-based substrate amended with various composts and with both liquid organic and conventional hydroponic fertilizers. They found in their first year's experiment that after 1 month their organically treated plants, which had received steady organic liquid supplement of K, Ca, Mg, and S from the time of transplanting, displayed N and P deficiency symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of each include blood meal, bone meal, milled poultry feathers, digested sewage sludge, and algae; and soybean oil, guanos, worm compost tea, and fish emulsion, respectively (Bi et al, 2010;Burger et al, 1997;Eaton et al, 2013;Gagnon and Berrouard, 1994;Gravel et al, 2012;Hartz and Johnstone, 2006;Montagu and Goh, 1990;Zhai et al, 2009). Commercially available bio-based fertilizers contain these materials, or more commonly, combinations of multiple components .…”
Section: Bio-based Fertilizers For Container-crop Productionmentioning
confidence: 99%
“…Furthermore, breakdown and release of nutrients happen more quickly as fertilizer particle size is decreased and occur quickest when fertilizers are applied as liquids (Montagu and Goh, 1990;Gravel et al, 2012). Liquid organic fertilizers rapidly release nutrients upon application, but possess limited sustained nutrient release (Hartz et al, 2010;Zhai et al, 2009). This necessitates consistent and repeated applications of liquid fertilizer for adequate plant nutrition if they are not used in conjunction with a slower-releasing fertilizer (Gravel et al, 2012).…”
Section: Bio-based Fertilizers For Container-crop Productionmentioning
confidence: 99%